Novel evidence for Retinoic Acid-Induced G (Rig-G) as a tumor suppressor by activating p53 signaling pathway in lung cancer - Sun, Junjun (FASEB J, 2020)
Lung cancer is one of most common malignancies worldwide. We have previously identified retinoic acid-induced gene G (Rig-G) as a tumor suppressor in not only acute promyelocytic leukemia, but as well in other solid tumors. However, the clinical significance of Rig-G and the underlying mechanism(s) for its biological function in lung cancer remain largely unexplored. Herein, we first compared the expression of Rig-G between lung cancer (n=138) and normal tissues (n=23), from public-available datasets and our patient cohort. We further analyzed the correlation of Rig-G expression with key clinico-pathological features and survival outcomes in a multi-site clinical cohort of 300 lung cancer patients. Functional studies for Rig-G were performed in cell lines, and an animal model to support clinical findings. We found that Rig-G was frequently downregulated in lung cancer tissues and cell lines, and correlated with poor prognosis in lung cancer patients. Overexpression of Rig-G led to significantly reduced cell growth and suppressed migration in A549 and NCI-H1944 cells, accompanied by reduced epithelial-mesenchymal transition. Likewise, restoration of Rig-G in Lewis lung carcinoma cells permitted development of fewer cancer metastases vs. controls in an animal model. Gene expression profiling results identified p53 pathway as a key downstream target of Rig-G, and p53 inhibition by pifithrin-α caused abrogation of tumor-suppressive effects of Rig-G in lung cancer. In conclusion, we for the first time have identified Rig-G as a novel and important tumor suppressor, which may serve as a potential therapeutic target for restoring p53 expression in lung cancer patients.